Personalization of the Microbiota of Donor Human Milk with Mother’s Own Milk - Cacho, Nicole T.; Harrison, Natalie A.; Parker, Leslie A.; Padgett, Kaylie A.; Lemas, Dominick J.; Marcial, Guillermo E.; Li, Nan; Carr, Laura E.; Neu, Josef; Lorca, Graciela L. (Frontiers in Microbiology, 2017)
The American Academy of Pediatrics recommends that extremely preterm infants receive mother’s own milk (MOM) when available or pasteurized donor breast milk (DBM) when MOM is unavailable. The goal of this study was to determine whether DBM could be inoculated with MOM from mothers of preterm infants to restore the live microbiota (RM). Culture dependent and culture independent methods were used to analyze the fluctuations in the overall population and microbiome, respectively, of DBM, MOM, and RM samples over time. Using MOM at time=0 (T0) as the target for the restoration process, this level was reached in the 10% (RM-10) and 30% (RM-30) mixtures after 4 h of incubation at 37 °C, whereas, the larger dilutions of 1% (RM-1) and 5% (RM-5) after 8 h. The diversity indexes were similar between MOM and DBM samples however, different genera were prevalent in each group. Interestingly, 40% of the bacterial families were able to expand in DBM after 4 h of incubation indicating that a large percentage of the bacterial load present in MOM can grow when transferred to DBM however, no core microbiome was identified. In summary, the microbiome analyses indicated that each mother has a unique microbiota and that live microbial reestablishment of DBM may provide these microbes to individual mothers’ infants. The agreement between the results obtained from the viable bacterial counts and the microbiome analyses indicate that DBM incubated with 10 to 30% v/v of the MOM for 4 h is a reasonable restoration strategy.